Learning from our failures in blood–brain permeability: what can be done for new drug discovery?. (March 2015) - Martel, Sylvain
<x xml:space="preserve">Abstract</x> Many existing pharmaceuticals are rendered ineffective in the treatment of cerebral diseases due to a permeability barrier well known as the blood–brain barrier (BBB). Such barrier between the blood within brain capillaries and the extracellular fluid in brain tissue has motivated several approaches aimed at delivering therapeutics to the brain. These approaches rely on strategies that can be classified as molecular modifications, the use of BBB bypassing pathways, and BBB disruptions. Although several of these approaches that have been investigated so far show promising results, none has addressed the optimization of the ratio of the dose of the drug molecules that contributes to the therapeutic effects. As such, the extensive research efforts, such as prioritizing the enhancement of the BBB permeability alone is likely to fail to provide the best therapeutic effects for a given dose if prior systemic circulation is not avoided while enhancing the spatial targeting only to regions of the brain that need treatment. Hence, new therapeutics for the brain could be synthesized to take advantage of recent technologies for non-systemic delivery and spatially targeted brain uptake.